2013
DOI: 10.1037/a0031592
|View full text |Cite
|
Sign up to set email alerts
|

Perceived racial discrimination, but not mistrust of medical researchers, predicts the heat pain tolerance of African Americans with symptomatic knee osteoarthritis.

Abstract: Objective Studies have shown that perceived racial discrimination is a significant predictor of clinical pain severity among African Americans. It remains unknown whether perceived racial discrimination also alters the nociceptive processing of painful stimuli, which, in turn, could influence clinical pain severity. This study examined associations between perceived racial discrimination and responses to noxious thermal stimuli among African Americans and non-Hispanic whites. Mistrust of medical researchers wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 42 publications
4
55
0
Order By: Relevance
“…We previously reported that perceived racial discrimination was inversely associated with heat pain tolerance levels in AA persons with knee OA (11). We hypothesized that this relationship may be related to physiological changes in neuroendocrine functioning as a consequence of chronic stress associated with perceived racial discrimination.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously reported that perceived racial discrimination was inversely associated with heat pain tolerance levels in AA persons with knee OA (11). We hypothesized that this relationship may be related to physiological changes in neuroendocrine functioning as a consequence of chronic stress associated with perceived racial discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire asks, “Have you ever experienced discrimination, been prevented from doing something, or been hassled or made to feel inferior in any of the following situations because of your race, ethnicity, or color?” This question is followed by 9 response options (e.g., at school, getting hired or getting a job, bank loans, etc.). Respondents also chose from the following responses, “never,” “once,” “two or three times,” or “four or more times.” Although there are additional ways to score this questionnaire (16), the frequency of experiences was chosen to be consistent with previous studies (11, 15). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Demographic factors including sex, BMI, and indicators of socioeconomic status have all been shown to contribute to the experience of pain(25–28). Psychosocial factors have also been demonstrated to influence experimental pain, such as depressed mood and subjective experiences of discrimination(29,30). …”
Section: Methodsmentioning
confidence: 99%